From Clicks To Clients: The Role Of Task–Technology Fit And User Experience In Driving Competitive Advantage For Bali Tour Operators - Sawitri, Margareta Asri; Agustina, Ni Ketut Wiwiek (Politeknik Pariwisata Bali, 2025)
The digital era has transformed tourism; however, travel agents in Bali face challenges in technology adoption due to its misalignment with their specific work requirements. This study investigates the relationship between task characteristics, task-technology fit, and user experience in relation to travel agent services in Bali. Using a quantitative approach with a survey method of 68 travel agent employees, this study analyzed data using PLS-SEM. The study's results demonstrate that task characteristics have a positive and significant impact on user experience and task-technology fit. Task-technology fit also has a positive and significant impact on user experience, acting as a complementary mediator in the relationship between task characteristics and user experience. These findings provide practical implications for the management of travel agents in Bali to optimize the implementation of technology that is in line with the characteristics of employee duties, thereby improving operational efficiency and service quality in the face of the dynamics of the tourism industry.